Amish secrets - Perry, Marta (Perry, Marta. River Haven, 2020)
"Rachel Hurst sacrificed the life she wanted to stay home and care for her father and siblings after her mother's death. But now her father has decided to remarry, and there's no room for Rachel. Desperate to find a job, she accepts the position of housekeeper for a wealthy elderly woman in her isolated mansion. Jacob Beiler thought he had gotten over Rachel's rejection, but when she arrives as the new housekeeper, he is battered by both joy and bitterness at seeing her again. When odd near accidents threaten the elderly woman's well-being, her relatives are quick to point fingers, but Rachel suspects someone is intent on harming her employer. When no one believes her, the only person she can turn to for help is Jacob. With danger deepening, Rachel faces a situation that could cost her life...and will certainly break her heart once again."--Page 4 of cover.